The legal system of found property- An analytical study in the English law with the Islamic jurisprudence and the Iraqi civil law - علي يونس صلاح الدين (Journal of Legal Sciences, 2021)
The legal system of found property is considered as a reason or method of preliminary acquisition of ownership, as well as two other reasons, that is to say, the fixture of personal chattels, and the adverse possession, resting on the principles of equity, and included within the English common law of customary origins, which is unwritten and based upon judicial precedents of the English courts, equity and later legislations. It is worth-bearing in mind that the found property is the lost property on which the finder enjoys more rights than all other people, except its original owner. It is also worth-mentioning that the treasure trove is considered as found property in the English law. and it is any object at least 300 years old when found, which is not a coin but has metallic content of which at least 10 per cent by weight is precious metal. Meanwhile the Islamic jurisprudence regulated the legal system of found property accurately and in details, and considered it as the lost property, whose true owner is unknown. Whereas the Iraqi civil law No. (40) of 1951, referred to the found property , but did not regulate it, and left its regulation to special laws.